1978
DOI: 10.1002/kin.550101107
|View full text |Cite
|
Sign up to set email alerts
|

Autooxidation of diethyl hydroxylamine

Abstract: The autooxidation of diethy1 hydroxylamine (DEHA) has been studied both in solution and in the gas phase between 0" and 60°C. The results obtained are interpreted in terms of a nonchain free radical mechanism in which reaction (1) (1)is the rate-determining step. This reaction is followed by the reaction of H02 radicals with DEHA to give hydrogen peroxide. The initial stoichiometry is given by 2DEHA + 0 2 -2 nitrone + 2H20 which implies that the hydrogen peroxide reacts with DEHA to give water and diethyl nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…The authors reported an apparent activation energy (E a ) for DEHA in chlorobenzene solutions, ranging from 273 to 330 K, to be 16.5 ± 2.0 kcal mol −1 . 6 Remarkably, this value aligns closely with the estimated E a for hydrazine in the aqueous phase at elevated temperatures (from 380 to 573 K) as reported by Buxton and Stuart, which was 16.7 ± 1.2 kcal mol −1 . 9 Interestingly, these orders of magnitude for E a correspond with the energy barrier estimates for the first proton abstraction step of hydrazine in the gas phase, as recently computed by Asgharzade et al using quantum chemistry methods.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…The authors reported an apparent activation energy (E a ) for DEHA in chlorobenzene solutions, ranging from 273 to 330 K, to be 16.5 ± 2.0 kcal mol −1 . 6 Remarkably, this value aligns closely with the estimated E a for hydrazine in the aqueous phase at elevated temperatures (from 380 to 573 K) as reported by Buxton and Stuart, which was 16.7 ± 1.2 kcal mol −1 . 9 Interestingly, these orders of magnitude for E a correspond with the energy barrier estimates for the first proton abstraction step of hydrazine in the gas phase, as recently computed by Asgharzade et al using quantum chemistry methods.…”
Section: Introductionsupporting
confidence: 90%
“…Regarding DEHA for instance, two different scavenger mechanisms have been reported. The first mechanism, proposed by Cáceres et al is based on a rate-determining step of first-order kinetics that yields the HO 2 • radical The authors reported an apparent activation energy ( E a ) for DEHA in chlorobenzene solutions, ranging from 273 to 330 K, to be 16.5 ± 2.0 kcal mol –1 . Remarkably, this value aligns closely with the estimated E a for hydrazine in the aqueous phase at elevated temperatures (from 380 to 573 K) as reported by Buxton and Stuart, which was 16.7 ± 1.2 kcal mol –1 .…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Oxygen and Peroxides Diethylhydroxylamine (DEHA), because of its rapid reaction with alkyl, alkoxy, or peroxy radicals or with air to produce diethyl nitroxide (446), captured interest for its potential as a combatant of photochemical smog brought about by oxidation of nitrogen oxides in the presence of hydrocarbons (eq 336) . 344,345 (C2H5)!^+ Apparently all hydroxylamines with a free hydroxyl group at nitrogen attached to one or two hydrocarbon groups is subject to air oxidation. Nitroxide formation generally required the absence of hydrogen attached to either nitrogen or the a-carbon atom.3346 Such a hindered hydroxylamine (447) is the precursor to 4,4-dimethyloxazolidine-A/-oxy (doxyl) (448) in a new preparation of the latter in four steps from 4,4-dimethyloxazoline (eq 337) .…”
Section: A Electrochemical Oxidationmentioning
confidence: 99%